Gender-Specific Differences in Signs and Symptoms of Dry Eye Disease. (4th March 2021) - Borrelli, Maria; Frings, Andreas; Geerling, Gerd; Finis, David
ABSTRACT: Introduction: Dry eye disease (DED) is a multifactorial disease of the ocular surface characterized by loss of homeostasis of the tear film. Epidemiological studies suggest it occurs more frequently in women than men. The aim of this retrospective analysis was to determine whether patients with DED show gender-specific differences in symptoms and signs. Material and Methods: A retrospective analysis of 107 patients was conducted at the Department of Ophthalmology of the University of Düsseldorf – Germany. After completing the OSDI questionnaire, the patients underwent objective refraction and were asked about the following symptoms: burning, itching, foreign body sensation, epiphora, sticky eyes, pain, red eyes and swollen eyelids. Furthermore, they underwent an evaluation of the following signs: lipid layer thickness, non-invasive break-up-time (NI-BUT), conjunctival hyperemia, lid parallel conjunctival folds, meibography, Schirmer test and tear meniscus height, ocular surface staining, expressibility of meibomian glands. Results: Of the 107 patients (56.2 ± 17.3 years) 75 were women and 32 men. Women reported significantly more often eyelid swelling ( p = .03) and showed a tendency to complain more about red eyes ( p = .051), while men tended to complain more often about epiphora ( p = .053). In an age-matched sample taken from the cohort, significant differences were found for OSDI-scores ( p = .025) showing women reporting more symptoms compared to men, while men showed more conjunctival hyperaemia ( p = .004) than women. Women showed a significant thicker lipid layer ( p = .0009) in the full cohort, but not in the age-matched sample ( p = .43). Conclusion: Although the majority of the investigated parameters did not show gender-specific differences, women reported higher OSDI scores. These findings could be explained by an increased frequency of neuropathic symptoms or ocular surface sensitivity in women or higher resilience of men to consult an ophthalmologist. Sex may have an effect on the clinical characteristics of DED, but further studies are needed to confirm these findings.